Features of Marketing Activity of Producers in Conditions of Globalization - Savych, Oleksandr (TNEU, 2015)
Producers are basic subjects of the world commodity market which carry significant part of world economy added value. All industrial companies are working in hard competitive conditions. The modern feature of any company activity is global processes` influence: competition from global companies’ side (transnational corporations), global preferences of consumers, necessity in production of standardization and high qualitative commodities, necessity in development of single global or regional marketing strategy and marketing mix. The modern state of industrial companies ‘marketing management has been considered at the article, problems of marketing management dedicated to globalization and strong competition have been determined. Modern features of the globalization and its influence at marketing management of industrial businesses have been studied at the article.
Keywords: management; marketing; globalization; transnational corporations; industrial companies